2001
DOI: 10.1097/00007632-200108010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Notch Sensitivity of Titanium Alloy, Commercially Pure Titanium, and Stainless Steel Spinal Implants

Abstract: Caution is recommended when bending TI or CP rods, or placing a connector and removing it when using CP rods in situations in which fatigue failure is a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 15 publications
5
49
0
1
Order By: Relevance
“…In addition, fixation rods in the setting of PSO are often bent to angles of 20° to 60° and may be notched by the bending instruments. Previous studies have demonstrated that CC and TA have greater fatigue life than SS, 27,45 that TA is very notch sensitive, 14,27 and that bending rods lowers their performance. 5,21,25,30 Compared with TA and SS, CC has the greatest elastic modulus and displays the greatest ultimate stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fixation rods in the setting of PSO are often bent to angles of 20° to 60° and may be notched by the bending instruments. Previous studies have demonstrated that CC and TA have greater fatigue life than SS, 27,45 that TA is very notch sensitive, 14,27 and that bending rods lowers their performance. 5,21,25,30 Compared with TA and SS, CC has the greatest elastic modulus and displays the greatest ultimate stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although data thus far seem to indicate that selected adults with spinal deformity do have significant potential for improvement with surgical treatment, overall complication rates remain high and represent areas for continued improvement 7,8,32,[39][40][41][42][43] Despite great advances, an important source of complications and patient morbidity remains the inherent limitations of the durability of spinal implants. 1,3,4,6,[13][14][15][16][17][19][20][21]23,[25][26][27]30,32,33,38,[44][45][46][47]50,51 Although development of rod fracture may have significant consequences for patients, including pain, loss of deformity correction, and the need for revision surgery, the literature regarding rod fracture remains relatively limited. 1,4,9,11,15,19,23,29,38,49,51,52 Previous reports discussing rod fracture have...…”
mentioning
confidence: 99%
“…We used titanium rods as replacements in all cases of rod breakages. Several investigators have noted that titanium rods have the advantages of magnetic resonance imaging compatibility and increased rigidity, but are prone to microfracture propagation and are notch-sensitive in bending 6,16) . Stainless steel rods are thus used in most patients, except for those with infections or tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Jutte et al [16] reported a 0.9% incidence of rod failure in 105 lumbar or lumbosacral fusions, and in most other reports, rod fractures occurred after posterior lumbar fusion surgery. Intraoperative rod contouring and corrective procedures using reduction devices are generally thought to be risk factors for the failure of spinal constructs, particularly with pure titanium or titanium alloy implants because of their notch sensitivity [10,18,19]. One reason that no rod fracture was observed in our cohort may be that we tried as much as possible to avoid bending the rod, taking maximal advantage of the polyaxial screw and offset connecting device (Fig.…”
Section: The Characteristics As For Cervical Instrumentation Failurementioning
confidence: 99%